Electrochemical device, electrode for electrochemical device, coating liquid for electrochemical device and use thereof
By using polymers with specific structure and molecular weight as binders, the performance degradation caused by binders in existing lithium-ion batteries is solved, high charge and discharge speed and durability are achieved, and the overall performance of the electrochemical device is improved.
Patent Information
- Application Number
- CN202080089513.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-07
- Filing Date
- 2020-12-24
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2040-12-24
AI Technical Summary
In the existing lithium-ion batteries, the adhesive causes the exposed surface area of the active substance to decrease, which hinders the contact between the electrolyte and the active substance, thereby reducing the charge and discharge speed and magnification characteristics. The adhesive has low durability and affects the battery performance.
A polymer with a specific structure and molecular weight is used as a binder to form a composite material layer of the electrochemical device to improve the charge and discharge speed and durability of the electrode.
It achieves high charge and discharge speed and durability, improves the rate characteristics, resistance retention rate and discharge retention rate, and optimizes the overall performance of the electrochemical device.
Smart Images

Figure CN114868284B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a non-aqueous electrochemical device such as a lithium ion primary battery and a lithium ion secondary battery, and also relates to an electrode for the electrochemical device, a coating liquid for forming a member for the electrochemical device, and the use thereof. Background Art
[0002] Typically, a non-aqueous electrochemical device such as a primary battery or a secondary battery has an outer body and electrodes and electrolytes sealed therein, which are used to embody the functions of the device. The electrode includes an active material layer and a current collector provided as required. The active material layer is sometimes a foil of a metal active material, and sometimes a composite material layer containing a granular active material. Since the granular active material is contained, the composite material layer is usually a porous material and is used in the device in a state impregnated with an electrolyte.
[0003] In most cases, the composite material layer contains a binder in addition to the active material. By making the composite material layer contain a binder, the granular active material can be retained in the composite material layer. As a binder, various substances have been proposed (for example, Patent Documents 1 and 2).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2003-272634;
[0007] Patent document 2: Japanese Patent Application Publication No. 2011-40318. Summary of the invention
[0008] Problem that the invention aims to solve
[0009] The binder is necessary to keep the active material well in the composite material layer, but it also has the property of damaging the performance of the device. That is, by impregnating the composite material layer with an electrolyte and contacting the granular active material, when the device is made to perform, the binder is attached to the surface of the active material, which causes the exposed surface area of the active material to become smaller in this state, hindering the contact between the electrolyte and the active material. As a result, the speed of charge and discharge is reduced, and the performance of the device such as rate characteristics is reduced.
[0010] In addition, the durability of the binder itself is low, which may impair the performance of the device. For example, when the binder deteriorates during the charge and discharge of the device, the device performance such as the resistance retention rate and the discharge capacity retention rate may be reduced.
[0011] Therefore, the object of the present invention is to provide an electrochemical device having high charge and discharge speed and high durability, and excellent performance such as rate characteristics, resistance retention rate, and discharge capacity retention rate, as well as an electrode, a coating liquid, and its use for constituting the electrochemical device.
[0012] Solutions for solving problems
[0013] The present inventors have conducted studies to solve the above problems and have found that the above problems can be solved by using a polymer having a specific structure and molecular weight as a material constituting a binder, thereby completing the present invention.
[0014] That is, the present invention is as follows.
[0015] [1] An electrochemical device, which is a non-aqueous electrochemical device,
[0016] The electrochemical device comprises a polymer (P) sealed inside the electrochemical device.
[0017] The polymer (P) is a polymer having a molecular structure containing a unit (P) represented by the following formula (P) and having a mass average molecular weight of more than 50,000.
[0018] [Chemical formula 1]
[0019]
[0020] In formula (P), R P It is a group having 1 to 20 carbon atoms.
[0021] [2] The electrochemical device according to [1], wherein the ratio of the above-mentioned unit (P) in the above-mentioned polymer (P) molecules is 50% by mass or more.
[0022] [3] The electrochemical device according to [1] or [2], wherein the polymer (P) comprises the R P The unit (P) is a unit which is a methyl group or an ethyl group.
[0023] [4] The electrochemical device according to any one of [1] to [3], wherein the polymer (P) comprises the R P The unit (P) is a unit which is a group having 3 to 20 carbon atoms.
[0024] [5] The electrochemical device according to any one of [1] to [4], wherein the polymer (P) comprises the R P The unit (P) is a unit having a crosslinked structure.
[0025] [6] The electrochemical device according to any one of [1] to [5], wherein the polymer (P) comprises the R P As the above-mentioned unit (P), a unit having a fluorine group is used.
[0026] [7] The electrochemical device according to any one of [1] to [6], further comprising an electrolyte solution, wherein the amount of the polymer (P) is 5 parts by mass or more per 100 parts by mass of the electrolyte solution.
[0027] [8] An electrode for an electrochemical device, which is a non-aqueous electrochemical device electrode comprising a particulate active material and a polymer (P),
[0028] The polymer (P) is a polymer having a molecular structure containing a unit (P) represented by the following formula (P) and having a mass average molecular weight of more than 50,000.
[0029] [Chemical formula 2]
[0030]
[0031] In formula (P), R P It is a group having 1 to 20 carbon atoms.
[0032] [9] The electrode for an electrochemical device according to [8], wherein the ratio of the above-mentioned unit (P) in the above-mentioned polymer (P) molecules is 50% by mass or more.
[0033]
[10] The electrochemical device electrode according to [8] or [9], wherein the polymer (P) comprises the R P The unit (P) is a unit which is a methyl group or an ethyl group.
[0034]
[11] The electrode for an electrochemical device according to any one of [8] to
[10] , wherein the polymer (P) comprises the R P The unit (P) is a unit which is a group having 3 to 20 carbon atoms.
[0035]
[12] The electrode for an electrochemical device according to any one of [8] to
[11] , wherein the amount of the polymer (P) is greater than 1 part by mass relative to 100 parts by mass of the particulate active material.
[0036]
[13] The electrode for an electrochemical device according to any one of [8] to
[12] , wherein the electrode for an electrochemical device comprises a current collector layer and a composite material layer comprising the particulate active material and the polymer (P).
[0037]
[14] The electrode for an electrochemical device according to
[13] , wherein the current collector layer is a metal layer.
[0038]
[15] The electrode for an electrochemical device according to
[13] or
[14] , wherein the current collector layer has an irregularity of Ry 500 nm or more on a surface in contact with the composite material layer.
[0039]
[16] A coating liquid for an electrochemical device, comprising a polymer (P),
[0040] The polymer (P) is a polymer having a molecular structure containing a unit (P) represented by the following formula (P) and having a mass average molecular weight of more than 50,000.
[0041] [Chemical formula 3]
[0042]
[0043] In formula (P), R P It is a group having 1 to 20 carbon atoms.
[0044]
[17] The coating liquid for an electrochemical device according to
[16] , wherein the ratio of the above-mentioned unit (P) in the above-mentioned polymer (P) molecule is 50 mass % or more.
[0045]
[18] The electrochemical device coating liquid according to
[16] or
[17] , wherein the polymer (P) comprises the R P The unit (P) is a unit which is a methyl group or an ethyl group.
[0046]
[19] The coating liquid for an electrochemical device according to any one of
[16] to
[18] , wherein the polymer (P) comprises the R P The unit (P) is a unit which is a group having 3 to 20 carbon atoms.
[0047]
[20] The electrochemical device coating liquid according to any one of
[16] to
[19] , wherein the polymer (P) comprises the R P The above-mentioned unit (P) is a unit having a group having a crosslinkable partial structure.
[0048]
[21] The electrochemical device coating liquid according to any one of
[16] to
[20] , wherein the electrochemical device coating liquid has a slurry-like property.
[0049]
[22] An insulating layer for an electrochemical device, comprising a layer formed by curing the coating liquid according to any one of
[16] to
[21] .
[0050]
[23] The insulating layer according to
[22] , wherein the insulating layer contains a cross-linked product of the polymer (P) formed by the curing.
[0051]
[24] An electrode for an electrochemical device, comprising a layer formed by curing the coating liquid according to any one of
[16] to
[21] .
[0052]
[25] The electrode according to
[24] , wherein the electrode comprises a cross-linked product of the polymer (P) formed by the curing.
[0053]
[26] A primer layer for an electrochemical device, comprising a layer formed by curing the coating liquid according to any one of
[16] to
[21] .
[0054]
[27] The primer layer according to
[26] , wherein the primer layer comprises a cross-linked product of the polymer (P) formed by the curing.
[0055]
[28] An electrolyte for an electrochemical device, comprising a polymer (P),
[0056] The polymer (P) is a polymer having a molecular structure containing a unit (P) represented by the following formula (P) and having a mass average molecular weight of more than 50,000.
[0057] [Chemical formula 4]
[0058]
[0059] In formula (P), R P It is a group having 1 to 20 carbon atoms.
[0060]
[29] The electrolyte for an electrochemical device according to
[28] , wherein the ratio of the above-mentioned unit (P) in the above-mentioned polymer (P) molecules is 50% by mass or more.
[0061]
[30] The electrochemical device electrolyte according to
[28] or
[29] , wherein the polymer (P) comprises the R P The unit (P) is a unit which is a methyl group or an ethyl group.
[0062]
[31] The electrolytic solution for an electrochemical device according to any one of
[28] to
[30] , wherein the polymer (P) comprises the R P The unit (P) is a unit which is a group having 3 to 20 carbon atoms.
[0063]
[32] The electrolytic solution for an electrochemical device according to any one of
[28] to
[31] , wherein the polymer (P) comprises the RP The above-mentioned unit (P) is a unit having a group having a crosslinkable partial structure.
[0064] Effects of the Invention
[0065] According to the present invention, an electrochemical device having high charge and discharge speed, high durability, excellent rate characteristics, resistance retention, discharge capacity retention and other performances, as well as an electrode, a coating liquid and its use for constituting the electrochemical device are provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] Figure 1 It is a graph showing the experimental results of Reference Example 1 of the present invention. DETAILED DESCRIPTION
[0067] The present invention will be described in detail below by showing embodiments and examples. However, the present invention is not limited to the embodiments and examples described below, and can be arbitrarily modified within the scope of the present invention and its equivalent.
[0068] In the following description, the term "solvent" is understood in a broad sense and also includes the meaning of a dispersion medium. That is, "solvent" includes not only the medium in a solution (i.e., a mixture of a medium substance as a liquid and a substance as a solute dissolved and present therein), but also the medium in a dispersion (i.e., a mixture of a medium substance as a liquid and a substance as a dispersoid dispersed and present therein in the form of solid particles or emulsion particles), and the medium in a mixture containing both a solute and a dispersoid.
[0069] In the following description, unless otherwise specified, "(meth)acrylate" is a term including "acrylate", "methacrylate" and a mixture thereof.
[0070] [1. Overview of electrochemical device]
[0071] The electrochemical device of the present invention is a non-aqueous electrochemical device. That is, the electrochemical device of the present invention includes an electrode and an electrolyte solution contained in a sealed space inside a device container, and the contents are composed of liquids and solids other than water. The liquid contained in the device may also contain a trace amount of water, in which case the concentration is 10000 ppm or less, preferably 1000 ppm or less, and more preferably 500 ppm or less.
[0072] On the other hand, the container is a structural element for forming a closed space in the device, and its material is not particularly limited as long as it has physical properties that can form the internal space. Since the material constituting the container is not the material existing in the space inside the container, the material constituting the container is not included in the scope of the material enclosed in the electrochemical device.
[0073] [2. Polymer (P)]
[0074] The electrochemical device of the present invention contains a polymer (P) sealed therein. The polymer (P) has a molecular structure containing a unit (P) represented by the following formula (P).
[0075] [Chemical formula 5]
[0076]
[0077] In formula (P), R P It is a group having 1 to 20 carbon atoms. P It can be a straight chain, a branched chain, or a ring structure. P It may be a hydrocarbon group or a group containing elements other than carbon and hydrogen. P It may have an ether structure, an amine structure, or both in the chain. P It may also contain hetero atoms such as halogen atoms such as fluorine atoms.
[0078] R P Here, the cross-linked structure refers to the cross-linked structure between the polymer (P) and other R P The combined structure, therefore, in R P In the case of a cross-linked structure, there are multiple R P For example, as the polymer (P) contained in the material for manufacturing the electrochemical device of the present invention, a polymer having a cross-linked structure can be used. Alternatively, by using P The polymer (P) containing a crosslinkable partial structure can be prepared by subjecting the crosslinkable partial structure to a crosslinking reaction in the manufacturing process of the electrochemical device, thereby preparing an electrochemical device containing the polymer (P) containing a crosslinked structure. P , which can further improve the durability of the electrochemical device. Examples of partial crosslinking structures include carbon-carbon unsaturated bonds (double bonds or triple bonds), epoxy groups, oxetane groups, carboxyl groups, acetoacetyl groups, isocyanate groups, thiol groups, or combinations thereof. By having this structure, a crosslinking reaction can be induced to form a crosslink.
[0079] R P When the polymer (P) is used as a material of the composite material layer and the composite material layer further contains a carbon material such as a carbon active material, R PThe presence of an aromatic ring is preferred because the affinity of the polymer (P) to the carbon material is high. Examples of the aromatic ring include phenyl, naphthyl, anthracenyl, pyrenyl, and biphenyl, but are not limited thereto and may also include a ring having more carbon atoms than these.
[0080] In some ways, R P The number of carbon atoms in R is preferably 1 to 2. P The number of carbon atoms is in the range of 1 to 2, and in most cases, affinity with a suitable solvent can be obtained, and an electrochemical device having high charge and discharge speed, high durability, excellent rate characteristics, resistance retention, discharge capacity retention, etc. can be obtained. In addition, the polymer (P) can be well dissolved in a coating liquid using water as a solvent.
[0081] In some other ways, R P The number of carbon atoms in R is preferably 3 to 20. P The carbon number of the alkylene oxide is 3 to 20, and the lipophilicity of the polymer (P) can be increased. This is preferred when a polymer (P) having high lipophilicity is required.
[0082] As R P More specific examples include methyl, ethyl, propyl, butyl, alkyl groups having more carbon atoms than butyl, phenyl, oxyethylene chains, and fluorinated alkyl groups of various lengths. They may have a cyclic structure.
[0083] By properly choosing R P The type of the polymer (P) can be used to adjust the degree of hydrophilicity and other properties of the polymer (P). For example, by increasing the total R P By increasing the ratio of one or more of the methyl, ethyl, propyl and oxyethylene chains in the polymer (P), a highly hydrophilic polymer (P) can be obtained, for example, the polymer (P) can be made water-soluble. P The ratio of butyl or alkyl having more carbon atoms than butyl in the polymer (P) and phenyl in the polymer (P) can be increased to obtain a polymer (P) with high lipophilicity. P By increasing the ratio of the fluorine-containing groups in the polymer, a polymer (P) with high water repellency can be obtained.
[0084] The polymer (P) may be a homopolymer consisting of only one type of unit (P), a copolymer consisting of a plurality of types of units (P), or a copolymer consisting of one or more types of units (P) and units other than the units. When the polymer (P) is a copolymer, the copolymer may be in the form of a random copolymer, a block copolymer, a graft copolymer, or the like. When the polymer (P) contains units other than the units (P), examples of such units include (meth)acrylate units obtained by polymerizing (meth)acrylates such as methyl (meth)acrylate and ethyl (meth)acrylate.
[0085] However, when the polymer is a copolymer, the proportion of the unit (P) in the polymer (P) molecule is preferably more than 50% by mass, more preferably more than 60% by mass. The upper limit of the ratio can be 100% by mass. In addition, the molecular structure of the polymer (P) preferably includes a structure in which more than three units (P) are continuously combined. By having this structure, it is possible to obtain an electrochemical device with high charge and discharge speed and high durability, excellent performance such as rate characteristics, resistance retention, and discharge capacity retention.
[0086] The mass average molecular weight of polymer (P) is greater than 50000, preferably more than 100000, more preferably more than 150000, and further preferably more than 200000. The upper limit of the mass average molecular weight is not particularly limited, and can be less than 10000000. By making the mass average molecular weight more than the above lower limit, the mechanical strength of the device structural element containing polymer (P) can be improved, and an electrochemical device having high charge and discharge speed and high durability, excellent performance such as rate characteristics, resistance retention rate, and discharge capacity retention rate can be obtained. In particular, by making the mass average molecular weight a larger value above the above lower limit, good lubrication performance can be shown. By making the mass average molecular weight less than the above upper limit, the handleability of polymer (P) can be made good.
[0087] The molecular weight distribution of the polymer (P) is preferably 1.0 or more, more preferably 1.1 or more, and on the other hand, is preferably 10 or less, further preferably 5.0 or less, and further preferably 3.0 or less. The molecular weight distribution is a value represented by the ratio of the mass average molecular weight (Mw) to the number average molecular weight (Mn) (Mw / Mn). The molecular weight and molecular weight distribution values can be measured by GPC (gel permeation chromatography) using polyethylene oxide as a standard substance.
[0088] Although not being bound by a particular theory, the mechanism by which the effects of the present invention are obtained by including the polymer (P) in the electrochemical device of the present invention is considered to be as follows.
[0089] Since the unit (P) constituting the polymer (P) contains an amide structure (-CO-N), the polymer (P) has high heat resistance and can show strong adhesion to other components of the device such as the current collector, the spacer substrate, and the granular active material. Therefore, it is believed that the resistance to various stresses in the electrochemical device is improved. When the polymer (P) exists as a solid, it acts as an adhesive. In addition, when the polymer (P) exists in a liquid in a state of being dissolved or swollen due to the impregnation of the liquid, it exhibits viscosity and lubricity, and when the electrochemical device is subjected to internal or external forces, the degree of damage to the device caused by friction can be reduced. In addition, the polymer (P) has an extremely wide potential window (refer to Reference Example 1). This is also believed to be due to the inclusion of a chemically stable amide structure. In the case of introducing an electron-withdrawing substituent (such as fluorine) in the polymer (P), the oxidation resistance is further improved, and in the case of introducing an electron-donating substituent (such as a long-chain alkyl), the reduction resistance is further improved. Since when the molecular weight of polymer (P) is high, chemical reactivity and diffusion rate are low, the amount of reaction per unit time is reduced, and electrochemical stability is improved. In addition, the higher the molecular weight of polymer (P), the lower the ratio of chain ends with higher chemical reactivity, so it is preferred. More preferably, polymer (P) has a ring structure. If polymer (P) is used for electrochemical device, a device in which resistance is difficult to increase for a long time can be constituted. This is considered to be because it is not easy to hinder the movement of ions, so the degradation of the device is suppressed.
[0090] The method for producing the polymer (P) is not particularly limited and the polymer (P) can be produced by a known method. Examples of methods for producing the polymer (P) include: Ring-opening polymerization of compounds with oxazoline rings, acylation of polyethyleneimine, The polymerization of macromonomers with oxazoline chains and the graft polymerization initiated by polymers with initiating groups in the side chains. The macromonomer of the oxazoline chain can be copolymerized with other polymers to produce a block copolymer containing the unit (P) and other polymer units. Examples of polymers that can be copolymerized include silicone, polylactic acid, and polyethylene oxide.
[0091] When producing a polymer (P) having a crosslinked structure, a crosslinking reaction may be performed. Specifically, a partial structure having crosslinkability is used as R P A polymer (P) having a crosslinking structure can be obtained by using a polymer (P) having a crosslinking group or a polymer having other crosslinking groups as a material, and performing a crosslinking reaction suitable for the crosslinking structure. Examples of crosslinking reactions include photocrosslinking, thermal crosslinking, electron beam crosslinking, radiation crosslinking, and ion crosslinking.
[0092] As having Examples of the compound having an oxazoline ring include compounds represented by the following formula (P2).
[0093] [Chemical formula 6]
[0094]
[0095] R in formula (P2) P and its preferred embodiment and R in formula (P) P The terminal groups of the polymer (P) are not particularly limited and may be conventional The terminal groups obtained by ring opening of oxazoline derivatives may also be terminal groups obtained by adding or polymerizing various functional groups according to the selection of polymerization initiators and terminators, for example, alkyl groups such as methyl, hydroxyl groups, thiols, vinyl groups, alkynes, azides, piperazines, acrylates, methacrylates, epoxides, etc.
[0096] In the electrochemical device of the present invention, the polymer (P) can be present mainly in the composite material layer (i.e., the positive electrode composite material layer and / or the negative electrode composite material layer) as a binder for binding the granular active material. The polymer (P) can also be present in a layer other than the composite material layer, for example, in the insulating layer, as a binder for binding particles such as inorganic particles constituting the insulating layer. As a primer, the polymer (P) can be present as a layer inserted between two layers (for example, between the current collector and the composite material layer). According to the findings of the present inventors, by making the polymer (P) have the above-mentioned specific structure and molecular weight, the electrolyte can be well impregnated and perform well as a binder. As a result, an electrochemical device having a structural element (composite material layer, insulating layer, primer, etc.) containing a polymer (P) can be made into an electrochemical device having a high charge and discharge rate and high durability, and excellent performance such as rate characteristics, resistance retention rate, and discharge capacity retention rate.
[0097] In addition, the polymer (P) may also exist as a component of the electrolyte. In the electrochemical device of the present invention, when manufacturing the electrode composite material layer, a part of the polymer (P) as its component may exist in a state of being dissolved into the electrolyte. The mass of the polymer (P) in the electrochemical device of the present invention may be specified relative to the total amount of the electrolyte enclosed in the electrochemical device. Specifically, the amount of the polymer (P) may preferably be 5 parts by mass or more, more preferably 10 parts by mass or more, and further preferably 15 parts by mass or more relative to 100 parts by mass of the electrolyte. The upper limit of the amount of the polymer (P) relative to 100 parts by mass of the electrolyte is not particularly limited, for example, it may be 50 parts by mass or less. In the device, the polymer (P) exists mainly as a component of the electrode composite material layer, and when a part of the polymer (P) also exists in a state of being dissolved into the electrolyte, it is particularly preferred that the amount of the polymer (P) is above the above lower limit relative to the electrolyte. In this case, the dissolution of the polymer (P) from the electrode composite material layer can be suppressed, and the performance of the device can be maintained for a longer time.
[0098] Examples of the electrode having a composite material layer containing the polymer (P) in the electrochemical device of the present invention include the electrodes for electrochemical devices described below.
[0099] The electrochemical device of the present invention may have, in addition to the electrodes, structural elements generally included in an electrochemical device, such as an electrolyte and an insulating layer.
[0100] As the electrolyte, an organic electrolyte in which a supporting electrolyte is dissolved in an organic solvent is generally used. As an example of a supporting electrolyte in the case where the electrochemical device is a lithium ion secondary battery, a lithium primary battery, or an electrochromic device, a lithium salt can be cited. As an example of a lithium salt, LiPF6, LiAsF6, LiBF4, LiB(C2O4)F2, LiB(C2O4)2, LiSbF6, LiAlCl4, LiClO4, CF3SO3Li, C4F9SO3Li, CF3COOLi, (CF3CO)2NLi, (CF3SO2)3CLi, (FSO2)2NLi, (CF3SO2)2NLi, and (C2F5SO2)NLi can be cited. Among them, LiBF4, LiPF6, (CF3SO2)2NLi and (FSO2)2NLi are preferred because they are easily soluble in solvents and show a high degree of dissociation, and LiPF6, (CF3SO2)2NLi and (FSO2)2NLi are particularly preferred. As a supporting electrolyte, one may be used alone or two or more may be used in combination at any ratio.
[0101] When the electrochemical device is a capacitor, examples of the supporting electrolyte include the above-mentioned lithium salts and Salt. As Examples of the salt include triethylmethylammonium tetrafluoroborate, tetraethylammonium tetrafluoroborate, N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazole Tetrafluoroborate, 1-ethyl-3-methylimidazole Bis(trifluoromethanesulfonyl)imide, N,N-diethyl-N-methyl-N-(2-methoxyethyl)-tetrafluoroborate, etc., but not limited to these, other nitrogen cations, phosphorus cations, etc. can be used. As a supporting electrolyte, one can be used alone, or two or more can be used in combination at any ratio.
[0102] When the electrochemical device is another device, a supporting electrolyte containing carrier ions of the device may be selected.
[0103] As an organic solvent of a component of the electrolyte, a solvent capable of dissolving the supporting electrolyte can be appropriately selected. Examples of organic solvents include carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC), and ethyl methyl carbonate (EMC); esters such as γ-butyrolactone and methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; sulfur-containing compounds such as cyclopentane and dimethyl sulfoxide; and mixtures thereof. Among them, carbonates are preferred because of their high dielectric constant and wide stable potential region. In particular, from the viewpoint of imparting ionic conductivity to the polymer (P), a mixture of ethylene carbonate and / or propylene carbonate and an organic solvent having a boiling point of less than 150°C is preferred. As an organic solvent, one may be used alone, or two or more may be used in combination in any ratio.
[0104] As described above, from the viewpoint of suppressing the dissolution of the polymer (P) in the electrolyte when using the device, an electrolyte containing the polymer (P) can also be used when manufacturing the device. In this case, the amount of the polymer (P) can be the same range as described above relative to the electrolyte. Specifically, the amount of the polymer (P) relative to 100 parts by mass of the electrolyte can be preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and further preferably 15 parts by mass or more. Relative to 100 parts by mass of the electrolyte, the upper limit of the amount of the polymer (P) is not particularly limited, for example, it can be 50 parts by mass or less.
[0105] The insulating layer can be arranged between the positive electrode and the negative electrode. By having an insulating layer, conduction caused by contact between the positive electrode and the negative electrode can be avoided. As the insulating layer, a known insulating layer used in an electrochemical device can be used. As an example of an insulating layer in the case where the electrochemical device is a lithium ion secondary battery, a separator described in Japanese Patent Publication No. 2012-204303 can be cited. From the viewpoint that a thin insulating layer can be formed, the ratio of the electrode active material inside the device can be increased, and the capacity per unit volume can be increased, as the material of the insulating layer, a porous film formed by a resin of a polyolefin system (polyethylene, polypropylene, polybutylene, polyvinyl chloride, etc.) is preferably used. Alternatively, it is also preferred that an insulating layer of a porous layer provided using the electrochemical device coating liquid of the present invention is further provided on the surface of the resin porous film.
[0106] As specific examples of the types of electrochemical devices of the present invention, various non-aqueous primary batteries, secondary batteries, double electric layer capacitors, double electric layer transistors, electrochromic display materials, electrochemical luminescent elements, electrochemical actuators and dye-sensitized solar cells can be cited. As examples of batteries, lithium primary batteries, lithium ion secondary batteries, lithium metal secondary batteries, sodium ion batteries, potassium ion batteries, magnesium ion batteries, aluminum ion batteries and air batteries can be cited. The battery is particularly preferably a lithium ion primary battery or a lithium ion secondary battery.
[0107] The manufacturing method of the electrochemical device of the present invention is not particularly limited, and the structural elements as described above can be used to manufacture according to the manufacturing method of a known device. For example, the positive electrode and the negative electrode can be overlapped by a separator, and the battery shape can be wound, folded, etc. as needed, placed in a battery container, and the electrolyte is injected into the battery container and sealed to manufacture the device. In order to prevent the internal pressure of the secondary battery from rising, overcharging and discharging, etc., fuses, PTC elements and other overcurrent protection elements, porous metal mesh, guide plates, etc. can be provided as needed. The shape of the device can be, for example, any of a coin type, a button type, a sheet type, a cylindrical type, a square type, a flat type, etc.
[0108] [3. Coating liquid for electrochemical device]
[0109] The coating liquid for an electrochemical device of the present invention is a coating liquid that can be used to form a layered structure such as an electrode, an insulating layer, or a primer layer, which is a structural element of an electrochemical device.
[0110] The coating liquid of the present invention contains a polymer (P). The polymer (P) and its preferred examples are the same as the polymer (P) and its preferred examples in the electrochemical device of the present invention described above. However, as the polymer (P) in the electrochemical device, in forming R PIn the case of a polymer having a cross-linked structure, it is particularly preferable to use R as the polymer (P) contained in the coating liquid from the viewpoint of ease of handling during production and ease of obtaining a cross-linked structure in the obtained product. P A polymer having a cross-linked partial structure.
[0111] The coating liquid of the present invention may also contain a solvent. Examples of the solvent include water, organic solvents such as N-methylpyrrolidone, and mixtures thereof. In the manufacturing process of the layered structure using the coating liquid, the solvent evaporates and is completely removed or only a trace amount remains.
[0112] The coating liquid of the present invention preferably has a viscosity of a specific high value. The viscosity is preferably 5 cP or more, more preferably 10 cP or more. The upper limit of the viscosity is not particularly limited, and may be, for example, 100,000 cP or less. The ratio of the polymer (P) in the coating liquid of the present invention is expressed as a ratio of polymer (P) to solvent of 5:95 or more, more preferably 7:93 or more, and further preferably 9:91 or more, expressed on a mass basis. The upper limit of the ratio of the polymer (P) is not particularly limited, and may be, for example, 50:50 or less. The viscosity is measured using a B-type viscometer at 25°C and 6 rpm. By making the viscosity above the above lower limit, a coating with less fragmentation and wear can be obtained.
[0113] The coating liquid of the present invention may have a slurry-like property. Specifically, insoluble particles and fibers are almost suspended in the entire coating liquid relative to the solvent constituting the coating liquid, have no fixed shape and exhibit fluidity. The preferred viscosity range of the slurry is 10 to 100,000 cP. By having a slurry-like property, it is possible to easily form a layered structure such as an electrode, including processes such as coating and drying of a current collector.
[0114] [4. Electrode coating liquid]
[0115] The electrode coating liquid (ie, a coating liquid that can be used to form an electrode) in the electrochemical device coating liquid of the present invention will be described. The electrode coating liquid may be a slurry-like coating liquid containing a particulate active material, a polymer (P), and a solvent.
[0116] As the active material constituting the granular active material, a substance known to be contained as an active material in the composite material layer of the electrode can be appropriately selected. In the case where the coating liquid is used to form a composite material layer of the positive electrode or the negative electrode of a lithium ion secondary battery, as examples of compounds constituting the active material for the positive electrode, compounds containing lithium atoms such as lithium cobalt oxide (LCO), lithium iron phosphate (LFP), and lithium titanate (LTO) can be cited. As examples of compounds constituting the active material for the negative electrode, graphite, amorphous carbon, silicon, silicon oxide, metallic lithium, etc. can be cited.
[0117] From the viewpoint that the electrode can well exhibit the desired performance, the particle size of the particulate active material is preferably 0.1 μm or more, more preferably 0.5 μm or more, and is preferably 50 μm or less, more preferably 40 μm or less. The particle size may be a number average particle size.
[0118] The ratio of the granular active material and the polymer (P) in the electrode coating liquid can be appropriately adjusted within the range in which the electrode can exert the desired performance. Specifically, relative to 100 parts by mass of the granular active material, the ratio of the polymer (P) is preferably greater than 1 part by mass, more preferably 1.5 parts by mass or more, on the other hand, preferably 20 parts by mass or less, more preferably 10 parts by mass or less. The coating liquid containing the polymer (P) has a viscosity that increases according to its concentration, so from the viewpoint of setting the concentration of the coating liquid within an appropriate range, the concentration of the polymer (P) can be appropriately adjusted. Compared with existing viscosity modifiers such as CMC (carboxymethyl cellulose), the increase in viscosity is slow due to the increase in the concentration of the polymer (P), so in the adjustment of the viscosity using the polymer (P), the viscosity can be easily adjusted. Furthermore, compared with existing viscosity modifiers such as CMC, the polymer (P) has a small degree of hindrance to the movement of ions in the composite material layer.
[0119] The electrode coating liquid may contain an optional component in addition to the particulate active material, the polymer (P) and the solvent. As the optional component, a component known to be contained in a composite material layer as a structural element of the composite material layer may be appropriately selected.
[0120] As an example of any component, various polymers known to be used as binders other than polymer (P) can be cited. By properly mixing the polymer, the mechanical strength of the composite material layer can be further improved. As an example of the polymer, PVDF (polyvinylidene fluoride), PVDF-HFP (vinylidene fluoride-hexafluoropropylene copolymer), PTFE (polytetrafluoroethylene), CMC (carboxymethyl cellulose), alginic acid, polyacrylic acid, PAN (polyacrylonitrile), SBR (-Lx) (styrene-butadiene rubber latex), NBR (-Lx) (nitrile-butadiene rubber latex), BR (-Lx) (butadiene rubber latex), ACR (-Lx) (acrylic rubber latex), polyethylene oxide and their combination. When the electrode coating liquid includes a binder other than polymer (P), the ratio of the polymer (P) in their total is preferably 10% by mass or more, more preferably 20% by mass or more. By making the ratio of polymer (P) above the above lower limit, sufficient ion conductivity can be given to the binder component.
[0121] Further examples of the optional components include particulate components that improve the function of the composite material layer, such as conductive materials. As the conductive material, known materials such as acetylene black, graphite, graphene, and carbon nanotubes can be used.
[0122] As examples of arbitrary components other than the above, thickeners, dispersants, leveling agents, antioxidants, defoamers, wetting agents, pH adjusting agents and combinations thereof can be cited. From the viewpoint of making the granular active material and polymer (P) exert the performance of the electrode coating liquid, it is preferred that the proportion of the arbitrary component is small. Specifically, the total ratio of the granular polymer, the conductive material and the polymer (P) relative to the total solid components (components other than the solvent, i.e., the non-volatile residual components when forming the composite material layer) in the electrode coating liquid is preferably 90% by mass or more, more preferably 95% by mass or more. The upper limit of this ratio can be 100% by mass.
[0123] The method for preparing the electrode coating liquid is not particularly limited, and the electrode coating liquid can be prepared by, for example, mixing the above-mentioned components.
[0124] [5. Electrodes for electrochemical devices]
[0125] The electrode of the present invention is an electrode that can become a structural element of the electrochemical device of the present invention described above. The electrode of the present invention may include a porous composite material layer and a current collector. The electrode of the present invention includes a granular active material and a polymer (P). The granular active material and the polymer (P) are usually components of the composite material layer. The composite material layer may also include any component used to constitute the electrode. The granular active material, the polymer (P), any component, their preferred examples, and their content ratio in the composite material layer are the same as those examples as the electrode coating liquid as described above.
[0126] The ratio of the particulate active material and the polymer (P) in the electrode of the present invention can be the same ratio as those in the electrode coating liquid as described above. That is, in the composite material layer, the ratio of the polymer (P) to 100 parts by mass of the particulate active material is preferably greater than 1 part by mass, more preferably 1.5 parts by mass or more, and on the other hand is preferably less than 20 parts by mass, more preferably less than 10 parts by mass.
[0127] However, during the manufacturing process of the device, after the time point when the electrode is immersed in the electrolyte is reached, as time passes, there is a situation where the polymer (P) gels inside the composite material layer, and there is also a situation where the polymer (P) dissolves from the composite material layer. Due to this dissolution, the ratio of the granular active material and the polymer (P) in the composite material layer can change over time. The dissolution amount of the polymer (P) and its speed can vary with various conditions such as the type of polymer (P), the amount of polymer (P) contained in the electrolyte, and the storage and use conditions of the device. The proportion of the polymer (P) during manufacturing can be made to be a value higher than the above lower limit, so that during the entire period of use of the device, the proportion of the polymer (P) in the composite material layer can also be above the above lower limit. In addition, as described above, during the manufacture of the device, by adding a polymer (P) to the electrolyte, the dissolution of the polymer (P) after manufacturing can be suppressed.
[0128] In the composite material layer, polymer (P) can exist in the same state in its entirety, or it can exist unevenly in a region of a part of the composite material inside. For example, polymer (P) can have a gradient of low concentration inside the composite material layer and high concentration on the surface of the composite material layer (exposed surface, or interface with other layers). In the case of having this gradient, the mechanical strength of the composite material layer surface can be effectively improved, particularly preferably. In the case of using polymers such as PVDF and CMC alone, there is also the possibility of increasing the strength due to uneven existence, but because ion permeability is not apparent, uneven existence may have an adverse effect on the characteristics of the device.
[0129] The thickness of the composite material layer in the electrode of the present invention can be appropriately adjusted to obtain desired performance. Specifically, the thickness of the composite material layer is preferably 5 μm or more, more preferably 10 μm or more, and preferably 1000 μm or less, more preferably 600 μm or less.
[0130] The current collector in the electrode of the present invention can be a metal foil. Examples of metals constituting the foil include copper, aluminum, lithium, stainless steel, titanium, molybdenum, iron and nickel. The thickness of the current collector is preferably 5 μm or more, more preferably 8 μm or more, and on the other hand, preferably 100 μm or less, more preferably 50 μm or less.
[0131] The electrode of the present invention may include any layer in addition to the composite material layer and the current collector. For example, it may include an undercoat layer between the composite material layer and the current collector. The undercoat layer will be described later.
[0132] The electrode of the present invention can be manufactured by solidifying the electrode coating liquid. Specifically, the electrode coating liquid is applied on the surface of the current collector to form a coating liquid layer, and the coating liquid layer is solidified to form a composite material layer. The solidification of the electrode coating liquid can be carried out by drying and heating the coating liquid layer to volatilize the solvent, and then pressurizing the layer as needed. As a polymer (P), when using a polymer (P) having a crosslinking group, a reaction forming a crosslinked structure is implemented as needed, thereby obtaining a composite material layer comprising a polymer (P) having a crosslinked structure.
[0133] When a press treatment is performed when forming a composite material, the conditions of the press treatment can be adjusted so that the density of the resulting composite material becomes a desired value. The density of the composite material layer can be, for example, 0.5 to 6.0 g / cm 3 . When the pressure treatment is performed, the granular shape of the granular active material is transferred to the current collector, and a concave-convex surface can be formed at its interface (i.e., the surface in contact with the composite material layer). The height of the concave-convex surface is preferably greater than 500nm, and more preferably greater than 800nm. The height value of the concave-convex surface is the maximum height Ry specified in JIS. The upper limit of the height of the concave-convex surface is not particularly limited and may be less than 3000nm. More preferably, the ten-point average roughness Rz is greater than 500nm. By forming the concave-convex surface, the particles of the active material, etc. are maintained, and the closeness between the composite material layer and the current collector can be improved. From the perspective of enhancing the closeness of the composite material layer, inhibiting shedding and peeling, and from the perspective of inhibiting the offset of the composite material layer and the current collector, it is preferred that there be concave-convex surface, and the concave-convex surface can be formed during pressing, and the use of a current collector foil having concave-convex surface in advance is also a preferred form. In order to form concave-convex surface on the current collector, mechanical processing such as striking and rubbing, and chemical treatment such as etching can be used.
[0134] [6. Insulation layer]
[0135] The insulating layer of the present invention has a layer formed by solidifying the coating liquid for the electrochemical device of the present invention. The insulating layer may be a layer of a multilayer structure, for example, comprising a resin layer formed of a porous resin generally used as a separator and a porous layer comprising a polymer (P) disposed on the surface thereof. In addition to the polymer (P), the porous layer may also contain particles such as non-conductive inorganic particles used as a constituent material of the porous membrane. By having such a structure, the insulating layer of the present invention can be well impregnated with an electrolyte and perform as a good insulating layer. The thickness of the porous layer comprising a polymer (P) in the insulating layer is preferably 200 μm or less. The lower limit of the thickness is not particularly limited and may be 1 μm or more. The coating liquid for forming the porous layer may be a liquid comprising a polymer (P), particles for forming a porous body and a solvent. By applying the liquid to the surface of the resin layer and solidifying it, a porous layer can be formed to obtain the insulating layer of the present invention.
[0136] [7. Primer]
[0137] Generally, the primer layer may be present as a layer between two layers constituting an electrochemical device (eg, between a current collector and a composite material layer).
[0138] The primer layer of the present invention is a layer formed by solidifying the coating liquid for electrochemical device of the present invention, or it may be composed of only a layer formed by solidifying the coating liquid for electrochemical device of the present invention. That is, the primer layer may be a primer layer having a structure of a single layer containing a polymer (P). The primer layer may be a primer layer containing conductive microstructures such as conductive particles or conductive fibers in addition to the polymer (P). The particle size of the conductive particles or the fiber diameter of the conductive fibers may be smaller than the particle size of the granular active material in the composite material layer. By having a primer layer between the current collector and the composite material layer, their mechanical adhesion can be improved and the resistance between them can be reduced. The coating liquid for forming the primer layer may be a liquid containing a polymer (P), conductive microstructures and a solvent. By applying the liquid on the surface of other layers such as the current collector and solidifying it, a primer layer can be formed.
[0139] Example
[0140] The present invention will be described in detail below with reference to the following examples. However, the present invention is not limited to the following examples, and can be arbitrarily modified without departing from the scope of the present invention and its equivalent.
[0141] In the following description, "%" and "part" indicating an amount are based on mass unless otherwise specified. In addition, unless otherwise specified, the operations described below are performed under the conditions of room temperature and normal pressure.
[0142] In the following, the following polymers were used as polymers. Among them, polymer 1, polymer 2, comparative polymer C1, comparative polymer C2, comparative polymer C3, comparative polymer C4, and comparative polymers C5 to C7 were purchased and used as they were.
[0143] Polymer 1: Poly-2-ethyl-2- Oxazoline (manufactured by Sigma-Aldrich, 373974, mass average molecular weight 500000, molecular weight distribution 3-4)
[0144] Polymer 2: Poly-2-ethyl-2- Oxazoline (manufactured by Sigma-Aldrich, 372854, mass average molecular weight 200000, molecular weight distribution 3-4)
[0145] Polymer 3: Poly-2-ethyl-2- Oxazoline (mass average molecular weight 60000)
[0146] Polymer 4: acrylic acid and poly-2-ethyl-2- Polymer of oxazoline ester (mass average molecular weight 200000)
[0147] Polymer 5: acrylic acid and poly-2-methyl-2- Polymer of oxazoline ester (mass average molecular weight 130000)
[0148] Polymer 6: Poly(ethyleneimine-2-ethyl Oxazoline) copolymer (mass average molecular weight 440000)
[0149] Comparative polymer C1: carboxymethyl cellulose (manufactured by Daicel Chemical Industries, Ltd., DAICEL1110)
[0150] Comparative polymer C2: poly-2-ethyl-2- Oxazoline (manufactured by Sigma-Aldrich, 741906, mass average molecular weight 10000, molecular weight distribution less than 1.5)
[0151] Comparative polymer C3: poly-2-methyl-2- Oxazoline (manufactured by Sigma-Aldrich, 795283, number average molecular weight 5000, molecular weight distribution less than 1.3)
[0152] Comparative polymer C4: polyethylene oxide (manufactured by Sigma-Aldrich, 181994, viscosity average molecular weight 200,000)
[0153] Comparative polymer C5: polyvinylidene fluoride (Solef (registered trademark) 5130 manufactured by Solvay Co., Ltd., mass average molecular weight 1,000,000)
[0154] Comparative polymer C6: poly-2-ethyl-2- Oxazoline (manufactured by Sigma-Aldrich, 372846, mass average molecular weight 50000, molecular weight distribution 3-4)
[0155] Comparative polymer C7: poly-2-ethyl-2- Oxazoline (manufactured by Sigma-Aldrich, 741884, mass average molecular weight 35000, number average molecular weight 25000, molecular weight distribution 1.4)
[0156] [Production Example 1: Polymer 3]
[0157] Poly-2-ethyl-2- Oxazoline and poly 2-ethyl-2- The oxazoline was mixed at a mass ratio of 4:1 to prepare a mixture. This mixture was used as polymer 3 below.
[0158] [Production Example 2: Polymer 4]
[0159] Poly-2-ethyl-2- Azoline (comparative polymer C7) was dissolved in dichloromethane and subjected to a dehydrochlorination reaction with acryloyl chloride at 25°C for 48 hours in the presence of triethylamine to obtain a macromonomer. The end of the oxazoline chain is bound to an acrylate of an acryloyl group. The macromonomer was polymerized in acetonitrile with azobisisobutyronitrile as an initiator at 60°C for 120 hours to obtain polymer 4. When the mass average molecular weight and molecular weight distribution of polymer 4 were measured by GPC, the mass average molecular weight was 200,000 and the molecular weight distribution was 2.3.
[0160] [Production Example 3: Polymer 5]
[0161] Poly-2-methyl-2- Azoline (comparative polymer C3) was dissolved in dichloromethane and subjected to a dehydrochlorination reaction with acryloyl chloride at 25°C for 48 hours in the presence of triethylamine to obtain a macromonomer. The macromonomer is a 2-methyl-2- The end of the oxazoline chain is bound to an acrylate of an acryloyl group. The macromolecular monomer was polymerized in water with V-50 (Fujifilm Wako Pure Chemical Industries, Ltd.) as an initiator at 60°C for 24 hours to obtain polymer 5. When the mass average molecular weight and molecular weight distribution of polymer 5 were measured by GPC, the mass average molecular weight was 130,000 and the molecular weight distribution was 2.0.
[0162] [Production Example 4: Polymer 6]
[0163] Partial hydrolysis of polymer 1 was performed. Specifically, polymer 1 was dissolved in 0.1 M hydrochloric acid and heated and stirred at 120° C. for 5 hours to obtain polymer 6 in which 12% of the amide structure was hydrolyzed to form an imine structure. The ratio of the hydrolyzed unit was given by 1 H-NMR calculations.
[0164] [Example 1-1]
[0165] (1-1-1. Positive electrode)
[0166] In a planetary mixer, 100 parts of LiFePO4 (granular active material; number average particle size 1 μm) as a positive electrode active material, 5 parts of acetylene black (HS-100, manufactured by Denki Kagaku Kogyo Co., Ltd.) as a conductive material, and 2 parts of a 9% aqueous solution of polymer 1 as a binding material, which is equivalent to 2 parts of the solid content of polymer 1, were added, and then ion exchange water as a dispersion medium was added and mixed to make the total solid content concentration 61% to prepare a slurry composition for a positive electrode of a lithium ion secondary battery.
[0167] The positive electrode slurry composition was coated on an aluminum foil with a thickness of 20 μm and Rz = 0.36 μm as the positive electrode current collector using a notch wheel coater at a coating amount of 8 mg / cm 2 The coating was performed to obtain a multilayer having a layer structure of (positive electrode current collector layer) / (positive electrode slurry composition layer). The multilayer was conveyed in an oven at 60°C at a speed of 0.5 m / min for 2 minutes to dry it, and then heated at 120°C for 2 minutes. Through this operation, a positive electrode raw material having a layer structure of (positive electrode current collector layer) / (positive electrode slurry dried material layer) was obtained.
[0168] The positive electrode raw material was pressed using a roller press. The pressing conditions were adjusted so that the density of the obtained positive electrode composite material layer was 2.00 g / cm 3 In order to remove the dispersion medium, the positive electrode raw material after the pressure treatment was placed in a vacuum environment at a temperature of 120° C. for 3 hours. Through this operation, a positive electrode having a layer structure of (positive electrode current collector layer) / (positive electrode composite material layer) was obtained.
[0169] (1-1-2. Secondary battery)
[0170] The positive electrode obtained in (1-1-1) was cut into a circle with a diameter of 12 mm to obtain a circular positive electrode.
[0171] A lithium metal foil (thickness 200 μm) was cut into a circular shape with a diameter of 14 mm to obtain a circular negative electrode.
[0172] A single-layer polypropylene spacer was cut into a circular shape having a diameter of 19 mm to obtain a circular spacer.
[0173] A stainless steel coin-shaped outer container having a polypropylene seal and a stainless steel cap having a thickness of 0.2 mm fitted to the opening of a button cell CR2032 was prepared.
[0174] A circular positive electrode, a circular separator and a circular negative electrode are stacked in sequence. The circular positive electrode is oriented so that the surface of the positive electrode composite material layer is in contact with the circular separator. The deposit is stored in an outer container. An electrolyte (solvent: EC / EMC=3 / 7 (mass ratio), electrolyte: LiPF6 with a concentration of 1M) is injected into the outer container so that no air remains in the container. The cap is fitted and fixed on the outer container through a seal, and the outer container is sealed to manufacture a lithium-ion secondary battery with a diameter of 20 mm and a thickness of about 3.2 mm. 160 mg of electrolyte is injected, and the excess electrolyte is wiped off.
[0175] (1-1-3. Discharge capacity retention rate)
[0176] The discharge capacity retention rate of the lithium-ion secondary battery produced in (1-1-2) was measured at a temperature of 25°C. A constant current charge and discharge of 0.1C was performed between 2.50 and 4.00V, and the discharge capacity C1 at this time was measured. After that, CC charging was performed at a constant current of 0.1C, and after reaching 4.0V, CV charging was performed until the current value reached 0.002C, and then the combination of charging and discharging operations at a constant current of 0.1C was continued. This charge and discharge was performed 10 times, and the discharge capacity C10 of the 10th time was measured. The discharge capacity retention rate ΔC = (C10 / C1) × 100 (%) was calculated from the values of C1 and C10. The larger the discharge capacity retention rate ΔC is and the closer it is to 100%, the higher the ability to maintain the discharge capacity is. The obtained discharge capacity retention rate ΔC is 99%.
[0177] (1-1-4.Resistance retention)
[0178] The resistance retention rate of the lithium-ion secondary battery produced in (1-1-2) is calculated in an environment with a temperature of 25°C. In the first cycle of the discharge capacity retention rate measurement in (1-1-3), the voltage during charging V1c, the voltage during discharging V1d in the first cycle, the voltage during charging V10c in the 10th cycle, and the voltage during discharging V10d in the 10th cycle are used to calculate the resistance retention rate ΔR = (V1c-V1d) / (V10c-V10d). The larger the resistance retention rate ΔR is and the closer it is to 1, the higher the ability to suppress the increase in resistance. The resistance retention rate ΔR obtained is 1.0.
[0179] (1-1-5. Mechanical stress resistance)
[0180] The positive electrode obtained in (1-1-1) was cut out to obtain a rectangular sample of 1 cm × 5 cm. The sample was immersed in an electrolyte (1MLiPF6, solvent: EC / EMC = 3 / 7 (mass ratio)). In the immersed state, the surface of the positive electrode composite material layer was bent outward to bend the sample. The degree of mechanical stress resistance was evaluated by observing the bent part. As a result, no shedding of the positive electrode composite material layer was observed.
[0181] (1-1-6. Presence of unevenness)
[0182] The positive electrode obtained in (1-1-1) was cut with a cross-section polisher to form a cross section parallel to the thickness direction, and observed with a scanning electron microscope. As a result, the particles of the positive electrode active material and the conductive material were sunken into the current collector layer, forming concave and convex. The roughness of the concave and convex was measured, and the maximum height Ry was 1.1μm and the ten-point average roughness Rz was 0.76μm.
[0183] [Examples 1-2 to 1-4]
[0184] The coating amount of the positive electrode slurry composition in (1-1-1) was changed to 10 mg / cm 2 (Example 1-2), 12 mg / cm 2 (Example 1-3), or 14 mg / cm 2 (Example 1-4) Except for this, the positive electrode raw material was obtained by the same operation as in (1-1-1) of Example 1-1. The mechanical stress resistance of the obtained positive electrode raw material was evaluated by the same operation as in (1-1-5) of Example 1-1. As a result, no fall-off of the positive electrode composite material layer was observed.
[0185] [Comparative Example 1-1]
[0186] A battery was obtained and evaluated by the same operation as in Example 1-1 except for the following changes.
[0187] ■In the production of the positive electrode of (1-1-1), comparative polymer C1 was used instead of polymer 1
[0188] ■The amount of ion exchange water added was changed so that the total solid content concentration of the slurry composition for lithium ion secondary battery positive electrodes was 50%.
[0189] The obtained discharge capacity retention rate ΔC was 99%.
[0190] The obtained resistance retention ratio ΔR was 2.0. That is, the resistance of the electrode increased by two times through 10 cycles of charge and discharge.
[0191] Mechanical stress resistance evaluation was performed. As a result, it was confirmed that the positive electrode mixture layer was peeled off from the bent portion, and the aluminum foil of the positive electrode current collector was exposed in a linear shape at the bent portion.
[0192] The roughness of the concavities and convexities was measured. As a result, the maximum height Ry was 1.2 μm and the ten-point average roughness Rz was 0.87 μm.
[0193] [Comparative Examples 1-2 to 1-4]
[0194] An attempt was made to obtain a positive electrode by the same operation as (1-1-1) of Example 1-1 except for the following changes.
[0195] ■In the production of the positive electrode of (1-1-1), comparative polymer C1 was used instead of polymer 1.
[0196] ■The amount of ion exchange water added was changed so that the total solid content concentration of the slurry composition for lithium ion secondary battery positive electrodes was 50%.
[0197] ■ The coating amount of the positive electrode slurry composition in (1-1-1) was changed to 10 mg / cm 2 (Comparative Example 1-2), 12 mg / cm 2 (Comparative Examples 1-3), or 14 mg / cm 2 (Comparative Examples 1-4).
[0198] However, in any of Comparative Examples 1-2 to 1-4, large cracks appeared in the direction along the coating direction of the notch wheel coater, and the positive electrode composite material layer peeled off from the current collector foil, and the positive electrode could not be obtained. This is believed to be because CMC cannot withstand the mechanical stress associated with dimensional changes caused by heating and drying.
[0199] [Examples 1-5 to 1-8]
[0200] A battery was obtained and evaluated by the same operation as in Example 1-1 except for the following changes.
[0201] ■ In the production process of the positive electrode of (1-1-1), instead of using 2 parts of polymer 1, 1 part of a mixture of polymer 1 and 1 part of CMC was used.
[0202] ■The amount of ion exchange water added was changed so that the total solid content concentration of the slurry composition for lithium ion secondary battery positive electrodes was 52%.
[0203] ■ The coating amount of the positive electrode slurry composition in (1-1-1) was changed to 10 mg / cm 2 (Example 1-6), 12 mg / cm 2 (Example 1-7), or 14 mg / cm 2(Example 1-8) (Example 1-5 remains unchanged, still 8 mg / cm 2 ).
[0204] The positive electrode was able to be produced without generating cracks (cracks generated in Comparative Examples 1-2 to 1-4).
[0205] [Example 2]
[0206] A battery was obtained and evaluated by the same operation as in Example 1-1 except for the following changes.
[0207] ■ In the production of the positive electrode of (1-1), 4 parts of polymer 2 were used instead of polymer 1.
[0208] In the case of this example, the discharge capacity retention ratio ΔC was 99% and the resistance retention ratio ΔR was 1.0. In addition, in the mechanical stress resistance, no fall-off of the positive electrode mixture layer was observed, and all items were equivalent to those of Example 1.
[0209] [Example 3]
[0210] A battery was obtained and evaluated by the same operation as in Example 1-1 except for the following changes.
[0211] ■ In the production process of the positive electrode of (1-1), 3 parts of polymer 4 were used instead of polymer 1.
[0212] In the case of this example, the discharge capacity retention ratio ΔC and the mechanical stress resistance can be expected to be equivalent to those of Example 1.
[0213] [Example 4]
[0214] A battery was obtained and evaluated by the same operation as in Example 1-1 except for the following changes.
[0215] ■ In the production process of the positive electrode of (1-1), 3 parts of polymer 5 were used instead of polymer 1.
[0216] In the case of this example, the discharge capacity retention ratio ΔC and the mechanical stress resistance can be expected to be equivalent to those of Example 1.
[0217] [Comparative Example 2]
[0218] In the process of manufacturing the positive electrode of (1-1), except that comparative polymer C2 was used instead of polymer 1, the battery was attempted to be manufactured by the same operation as in Example 1. In this case, when the positive electrode raw material was pressed by a roller press, the positive electrode slurry dried material layer was peeled off from the current collector layer, and cracks occurred in the positive electrode slurry dried material layer, and a positive electrode could not be obtained.
[0219] [Example 5-1]
[0220] In a planetary mixer, 100 parts of LiCoO2 (CELLSEED C, manufactured by Nippon Chemical Industry Co., Ltd., a granular active material; the number average particle size is 20 μm) as a positive electrode active material, 2.1 parts of acetylene black (HS-100, manufactured by Denki Kagaku Kogyo Co., Ltd.) as a conductive material, and 1.6 parts of an 8% NMP solution of polymer 1 as a binder material, based on the solid content of polymer 1, were added, and NMP as a dispersion medium was further added and mixed to make the total solid content concentration 81% to prepare a slurry composition for a positive electrode of a lithium ion secondary battery.
[0221] The positive electrode slurry composition was coated on a 20 μm thick aluminum foil as the positive electrode current collector using a notch wheel coater at a coating amount of 20 mg / cm 2 The coating was performed to obtain a multilayer having a layer structure of (positive electrode current collector layer) / (positive electrode slurry composition layer). As the aluminum foil, a strip of aluminum foil with a width of 12 cm was used, and the coating was performed in an area with a width of 8 cm in the center in the width direction, and the notched wheel coater was moved in a direction parallel to the length direction for coating.
[0222] The multilayered product was dried by conveying it in an oven at 60°C at a speed of 0.5 m / min for 2 minutes, and then heated at 120°C for 2 minutes. This operation gave a positive electrode material having a layer structure of (positive electrode current collector layer) / (positive electrode slurry dried product layer).
[0223] The positive electrode raw material was pressed using a roller press. The pressing conditions were adjusted so that the density of the obtained positive electrode composite material layer was 3.90 g / cm 3 In order to remove the dispersion medium, the positive electrode raw material after the pressure treatment was placed in a vacuum environment at a temperature of 120° C. for 3 hours. Through such an operation, a positive electrode having a layer structure of (positive electrode current collector layer) / (positive electrode composite material layer) was obtained.
[0224] The warpage of the obtained positive electrode was measured. The positive electrode was placed on a horizontal table with the positive electrode composite material layer facing upward, and the distance between the surface of the table and the center of the lower surface of the positive electrode composite material layer in the width direction was measured to measure the warpage. The warpage was 0.1 cm.
[0225] [Comparative Example 3]
[0226] As a binding material, an 8% NMP solution of comparative polymer C5 (the amount added is the same as in Example 5-1, and the comparative polymer C5 is 1.6 parts in terms of solid content) is used instead of an 8% NMP solution of polymer 1. In addition, the positive electrode is obtained by the same operation as in Example 5-1 and the warping amount is measured. The obtained positive electrode is arched in its width direction and has a large warping. This is considered to indicate that the residual amount of stress accompanying the processing experience is large. Because if the warping is large, the production of the electrochemical device will become difficult, it is not preferred. The warping amount is 1.8 cm.
[0227] [Example 5-2]
[0228] A positive electrode was obtained and the warpage amount was measured by the same operation as in Example 5-1 except for the following changes.
[0229] ■ As a binder, a combination of an 8% NMP solution of polymer 1 and an 8% NMP solution of comparative polymer C5 was used instead of using an 8% NMP solution of polymer 1. The amounts used were 0.8 parts based on the solid content of polymer 1 and 0.8 parts based on the solid content of comparative polymer C5, respectively.
[0230] The warping amount is 0.8 cm.
[0231] [Reference Example 1: Determination of Potential Window]
[0232] To confirm the The electrochemical stability of oxazoline was investigated by linear sweep voltammetry (LSV).
[0233] The polymer 1 was dissolved in 1M LiPF6 (solvent; EC / EMC=3 / 7, mass ratio) at a concentration of 10% to prepare a polymer solution.
[0234] The working electrode, counter electrode, and reference electrode were immersed in the polymer solution and the first potential scan was performed. As the working electrode, a conductive carbon-coated electrode with a surface area of 2 cm 2 (Size 1cm×1cm) aluminum foil. Use lithium metal foil as counter electrode and reference electrode. Rise from natural potential to relative to Li / Li at 1mV / s + Scan for 4.8V.
[0235] Next, the working electrode was changed to copper foil (surface area 2 cm2, size 1 cm×1 cm), and a second potential sweep was performed on Li / Li+ from the natural potential to -0.5 V at 1 mV / s.
[0236] The results are shown in Figure 1 .exist Figure 1 In the figure, the dotted line represents the result of the first potential scan, and the solid line represents the result of the second potential scan.
[0237] Depend on Figure 1 The results show that Oxazoline is at least 0~4.8V(vs Li / Li + ) is electrochemically stable over a wide potential range and is suitable as a material for electrochemical devices.
[0238] [Example 6: Thermal stress resistance]
[0239] The polymer 1 was dissolved in a 1M LiPF6 (solvent: propylene carbonate) electrolyte at a concentration of 6 mass % to prepare a polymer solution.
[0240] The initial viscosity η0 of the polymer solution was measured at 25°C using a B-type viscometer. After that, the polymer solution was placed in a thermostatic bath at 60°C for 100 hours, and the viscosity η1 at 25°C was measured again. The viscosity retention rate ((η1 / η0)×100(%)) was calculated from η0 and η1. The viscosity retention rate was 100%.
[0241] [Comparative Example 4]
[0242] The viscosity retention of the polymer solution was determined by the same operation as in Reference Example 2 except that Comparative Polymer C4 was used instead of Polymer 1. The viscosity retention was 30%, indicating that Comparative Polymer C4 had inferior heat resistance in the electrolyte solution compared to Polymer 1.
[0243] [Example 7: Alkali stress resistance]
[0244] NCA (LiNi 0.82 Co 0.15 Al 0.03 O2), acetylene black (AB) as a conductive aid, and polymer 2 were weighed in a mass ratio of positive electrode active material: AB: polymer 2 = 100: 2: 1.2, and an appropriate amount of N-methylpyrrolidone was added to these, and stirred with a planetary mixer to prepare a lithium ion secondary battery positive electrode slurry. Immediately after the preparation, the fluidity was confirmed at 25°C, and the result was confirmed to be flowing. After that, the positive electrode slurry was placed in an environment of 25°C for 24 hours, and the fluidity was confirmed again, and the result was confirmed to be flowing.
[0245] [Comparative Example 5]
[0246] The fluidity of the positive electrode slurry was confirmed by the same operation as in Example 7 except that comparative polymer C5 was used instead of polymer 2. The fluidity was confirmed at 25°C immediately after the preparation, and it was confirmed to be fluid. However, after storage, it was confirmed to be gel-like and non-flowing. This is considered to be due to the disappearance of the fluidity caused by the high pH of NCA, which caused the gelation of PVDP due to the dehydrofluoric acid reaction.
[0247] [Reference Example 2: Adhesion to substrate]
[0248] Polymer 3, comparative polymer C2 and comparative polymer C4 were dissolved in ion exchange water at 5% by mass to obtain three polymer solutions. Each polymer solution was applied to aluminum foil, copper foil and stainless steel (SUS304) foil and dried to obtain 9 coatings with a thickness of 50 microns. The coating was peeled off from the foil by scraping with tweezers.
[0249] Regarding the coating of polymer 3, the coating provided on all foils was not peeled off.
[0250] Regarding the coating film of comparative polymer C2, the coating film provided on all the foils fell off only at the portion scraped with tweezers.
[0251] Regarding the coating film of comparative polymer C4, the coating film provided on all the foils fell off in a film-like shape.
[0252] [Reference Example 3: Use with a non-ion-conductive polymer]
[0253] Polymer 1 and comparative polymer C5 were dissolved in N-methyl-2-pyrrolidone at various ratios to obtain five polymer solutions 1 to 5. In each of polymer solutions 1 to 5, the total concentration of polymer 1 and comparative polymer C5 was 8% by mass. In each of polymer solutions 1 to 5, the mass ratio of polymer 1 to comparative polymer C5 was 0:100 (polymer solution 1), 10:90 (polymer solution 2), 20:80 (polymer solution 3), and 50:50 (polymer solution 4).
[0254] Each polymer solution was cast onto a tray made of polytetrafluoroethylene, dried at 160°C, and N-methyl-2-pyrrolidone was distilled off to obtain a membrane with a thickness of 100 μm. The obtained membrane was immersed in 1M LiPF6 (solvent; EC / EMC=3 / 7, mass ratio) for 1 hour to allow the electrolyte to penetrate the membrane. After that, the membrane was pulled up, the remaining electrolyte was wiped off, and it was sandwiched between two SUS plates, and the ion conduction resistance was measured by the AC impedance method. The results were below the lower limit of measurement (polymer solution 1), 22Ω (polymer solution 2), 10Ω (polymer solution 3), 6Ω (polymer solution 4) and (polymer solution 5). In the case where the membrane does not contain polymer In the case of oxazoline polymers, no ionic conductivity is shown, but in the case of When the proportion of the oxazoline polymer in the entire membrane is 10 mass % or more, ion conductivity is observed. Azoline polymer, capable of forming ion-conducting pathways.
[0255] [Reference Example 4: Viscosity measurement of solution]
[0256] Polymers 1 to 3 and comparative polymer C2 were dissolved in ion exchange water at room temperature to obtain 5% aqueous solutions. The viscosities of these solutions were measured using a B-type viscometer at 6 rpm and 25°C and the results were 17, 6.6, 2.6, and 1.3 cP, respectively.
[0257] Each polymer solution was cast onto a tray made of polytetrafluoroethylene, dried at 160°C, and N-methyl-2-pyrrolidone was distilled off to obtain a film with a thickness of 100 μm. The obtained film was immersed in 1M LiPF6 (solvent; EC / EMC=3 / 7, mass ratio) for 1 hour to allow the electrolyte to penetrate the film. After that, the film was pulled up, the remaining electrolyte was wiped off, and it was sandwiched between two SUS plates to measure the ion conductivity resistance by the AC impedance method. The results were below the lower limit of measurement (polymer solution 1), 22Ω (polymer solution 2), 10Ω (polymer solution 3), 6Ω (polymer solution 4) and (polymer solution 5).
[0258] The membrane does not contain polymer In the case of oxazoline polymers, the membranes did not show ionic conductivity, whereas in the case of When the proportion of the oxazoline polymer in the entire membrane is 10 mass % or more, ion conductivity is observed. Azoline polymer, capable of forming ion-conducting pathways.
[0259] [Example 8: Production of coating liquid for insulating layer and production of insulating layer]
[0260] 100 parts of alumina particles having a volume average particle size of 0.6 μm, 1 part of a 1% aqueous solution of polymer 1 based on the solid content equivalent, and 2 parts of a 1% aqueous solution of comparative polymer C1 based on the solid content equivalent were added, dispersed using a bead mill, and mixed with ion exchange water to make the solid content concentration 25% to prepare a porous membrane slurry. The slurry was coated on a polyolefin spacer (Celgard 2325 manufactured by Polypore) and dried to obtain a composite spacer having an alumina layer with a thickness of 2 μm.
[0261] The composite separator was laminated to the positive electrode obtained in Example 5-1 and the2 The alumina was rubbed under a load of , and no alumina was observed to fall off from the separator or be transferred to the positive electrode, thereby obtaining a composite separator with little powder falling.
[0262] [Comparative Example 6]
[0263] A composite spacer was obtained in the same manner as in Example 8 except that only the comparative polymer C1 was used without mixing the aqueous solution of the polymer 1.
[0264] The composite separator was bonded to the positive electrode obtained in Comparative Example 3 and the 2 The composite separator was rubbed under a load of , and it was observed that the aluminum oxide fell off the separator and was transferred to the positive electrode in the form of particles. It can be seen that the composite separator had more powder falling than Example 8.
[0265] [Example 9: Preparation and application of primer solution]
[0266] 30 g of polymer 6 was added to 1000 g of ion exchange water and completely dissolved by stirring at 25 ° C for 2 hours. The solution was introduced into a bead mill with a cooling jacket, and zirconia balls with a diameter of 0.5 mm were added at a filling rate of 80%. 25 g of acetylene black (HS-100, manufactured by Denki Kagaku Kogyo Co., Ltd.) as conductive particles were added, and the product temperature was dispersed while not exceeding 40 ° C to obtain a conductive primer. A micro-gravure coater (μCoater, manufactured by Yasui Seiki Co., Ltd.) was used to apply the primer to an aluminum foil with a thickness of 20 μm and an etched surface (Rz = 4.6 μm) as a current collector, and it was dried to obtain a primer layer with a thickness of 1 μm after drying. The obtained primer layer was scraped with tweezers, and when the primer layer was tried to be peeled off from the foil, it was confirmed that there was no peeling and it was well adhered.
[0267] [Example 10]
[0268] 2 parts of polymer 1, 8 parts of electrolyte (solvent: EC / PC=5 / 5 (mass ratio), electrolyte: LiPF6 with a concentration of 1M), 100 parts of LiCoO2 (CELLSEED C, a granular active material; number average particle size 20μm) as a positive electrode active material, and 4 parts of acetylene black (HS-100, Denki Kagaku Kogyo Co., Ltd.) as a conductive material were weighed and fully mixed in a mortar to obtain a clay-like mixture. It was stretched and pasted on an etched aluminum foil (Rz=6μm) to produce a lithium ion secondary battery positive electrode with a mass of 21mg.
[0269] Next, 2 parts of polymer 1, 8 parts of electrolyte (solvent: EC / PC=5 / 5 (mass ratio), electrolyte: LiPF6 with a concentration of 1M), and 40 parts of graphite (MCMB made by MTI Corporation; number average particle size 18μm) as a negative electrode active material were weighed and fully kneaded in a mortar to obtain a clay-like kneaded product. The product was stretched and pasted on an etched copper foil (Rz=5μm) to produce a lithium ion secondary battery negative electrode with a mass of 11mg.
[0270] The positive electrode was cut into 10 cm × 10 cm, the negative electrode was cut into 10.2 cm × 10.2 cm, and a single-layer polypropylene separator impregnated with an electrolyte solution (solvent: EC / PC = 5 / 5 (mass ratio)) in which polymer 1 was dissolved at a concentration of 20% was cut into 10.4 cm × 10.4 cm. The separator was sandwiched between the positive electrode and the negative electrode to form a lithium ion battery. Even if the laminate is not specially fixed, the electrolyte contains polymer 1. The adhesive property is exhibited by the oxazoline, thereby maintaining a close contact state.
[0271] This was placed in an aluminum laminate outer container, and the opening was heat-sealed to produce a lithium ion secondary battery. In this step, no additional electrolyte was injected.
[0272] The lithium ion secondary battery can be stably charged and discharged at a charge and discharge rate of 1.0 C between 3.0 and 4.20 V in an environment with a temperature of 25° C.
[0273] [Example 11]
[0274] Prepare a 10% aqueous solution of polymer 1. Spray it onto a polypropylene spacer cut into 5 cm squares. The amount of polymer attached to the spacer is 0.1 mg / cm 2 The sprayed spacer is sticky in the undried state. When the spacer is attached to the positive electrode manufactured in Example 5-1 cut into 4.8 cm squares, it becomes one piece and is difficult to shift. On the other hand, in the case of a spacer not coated with a polymer, since the electrode and the spacer are not integrated, there is a problem of shifting during battery manufacturing. Oxazoline is ion-permeable and therefore does not block ion movement even when applied to the separator. However, when the same operation is performed using, for example, comparative polymer C1, the pores of the separator are clogged with an ion-impermeable membrane, which may reduce the output of the battery.
[0275] [Reference Example 5]
[0276] Polymer 1, Polymer 2, Comparative Polymer C6 and Comparative Polymer C7 were respectively dissolved in propylene carbonate to obtain a solution having a concentration of 5 wt %. The viscosity of the solution was measured at 25°C.
[0277] Subsequently, Li salt (LiTFSI; lithium bistrifluoromethanesulfonyl imide) was dissolved in each solution to prepare an electrolyte sample solution. The amount of Li salt added was 0.5 mol / kg relative to the mass of propylene carbonate. The viscosity of the electrolyte sample solution was measured at 25°C to determine the viscosity increase rate before and after the addition of Li salt. The results are shown in Table 1.
[0278] The solutions of any polymer showed a viscosity that was quite low compared to its concentration. By the subsequent addition of Li salt, the viscosity increase was confirmed in any solution, and in the case of a mass average molecular weight greater than 50,000, the viscosity increased significantly due to the addition of Li salt. This is believed to suggest that the interaction between polymer molecules is particularly strong in the range of a mass average molecular weight greater than 50,000, which is believed to be associated with the improvement of the stress tolerance of electrochemical devices and electrodes thereof.
[0279] [Table 1]
[0280] Table 1
[0281] polymer C7 C6 2 1 M 35000 50000 200000 500000 Solution viscosity (cP) 6.87 8.54 19.5 40.5 Solution viscosity with added Li salt (cP) 33.1 54.1 190 562 Viscosity increase rate (times) 4.8 6.3 9.7 13.9
Claims
1. An electrolyte for an electrochemical device, comprising a polymer (P), The polymer (P) is a polymer having a molecular structure containing a unit (P) represented by the following formula (P) and a mass average molecular weight greater than 50,000. The electrochemical device electrolyte is an organic electrolyte in which a supporting electrolyte is dissolved in an organic solvent. The supporting electrolyte is a lithium salt or Salt, The organic solvent is at least one selected from dimethyl carbonate, ethylene carbonate, diethyl carbonate, propylene carbonate, butylene carbonate, ethyl methyl carbonate, γ-butyrolactone, methyl formate, 1,2-dimethoxyethane, tetrahydrofuran, sulfolane, and dimethyl sulfoxide. The amount of the polymer (P) is 5 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass of the electrolytic solution for an electrochemical device, In formula (P), R P It is a methyl, ethyl, propyl, butyl, phenyl, or oxyethylene chain.
2. The electrolyte for an electrochemical device according to claim 1, wherein The ratio of the units (P) in the molecules of the polymer (P) is 50% by mass or more.
3. The electrolyte for an electrochemical device according to claim 1 or 2, wherein: The polymer (P) comprises the R P As the unit (P), a unit which is a methyl group or an ethyl group.
4. The electrolyte for an electrochemical device according to claim 1 or 2, wherein The polymer (P) comprises the R P The unit (P) is a unit which is a group having 3 to 20 carbon atoms.
Citation Information
Patent Citations
Nonaqueous secondary battery
JP2003272634A
Electrode for secondary battery, binder for secondary battery electrode, manufacturing method and secondary battery
JP2012204303A
Copolymer for binders for nonaqueous battery electrodes, slurry for nonaqueous battery electrodes, nonaqueous battery electrode, and nonaqueous battery
CN108475788A
Binder for electrochemical element
CN109997262A
Lithium secondary battery
JP2011040318A